Closing the gap: a call for a common blueprint for remote distance telesimulation. (12th April 2021) - Duff, Jonathan; Kardong-Edgren, Suzie; Chang, Todd P; Elkin, Rachel L; Ramachandra, Geethanjali; Stapleton, Stephanie; Palaganas, Janice C; Kou, Maybelle; Gross, Isabel T
Abstract : The physical requirements mandated by the COVID-19 pandemic have presented a challenge and an opportunity for simulation educators. Although there were already examples of simulation being delivered at a distance, the pandemic forced this technique into the mainstream. With any new discipline, it is important for the community to agree on vocabulary, methods and reporting guidelines. This editorial is a call to action for the simulation community to start this process so that we can best describe and use this technique.